Effect of the Microstructure of Support Materials on Cracking Catalyst Performance - Jianguo Bao; Wenxiu Rao; Yi Zhou; Bin Wen; Bo Wang; Guocheng Lv; Libing Liao (Crystals, 2023)
Fluid catalytic cracking (FCC) is a production process that converts petroleum into petroleum products in the presence of catalysts. The performance of an FCC catalyst plays a decisive role in petroleum refining. An FCC catalyst mainly comprises a molecular sieve (catalytic cracking active center), a carrier, and a binder. The carrier can enable the precracking of the heavy oil in its large pore, which can improve the overall activity of the catalyst and the conversion rate of heavy oil. The surface area and pore structure of carrier materials with different microscopic morphologies differ, which significantly affects the precracking of heavy oil molecules. Therefore, here, FCC catalysts were prepared using flake kaolinite, tubular halloysite, natural flake-tube-combined kaolinite, and mixed kaolinite as support materials, respectively. The FCC catalysts were used in FCC-heavy oil, and the influence of the carrier material morphology on the comprehensive performance of the catalysts was studied. The strength and cracking performance of the catalyst prepared using flake Maoming (M) were poor, whereas the catalyst prepared using tubular halloysite exhibited a good strength, high activity, and a good cracking ability for heavy oil. The catalyst prepared using natural flake-tube combined with Suzhou (S) exhibited a good strength and cracking performance, and it has been widely used in the industrial production of FCC catalysts. When 40% tube-like halloysite was mixed into M, the attrition of the prepared catalyst decreased by 0.5 units, the microreactivity increased by 1.4 units, the gasoline + liquefied petroleum gas (LPG) yield increased by 3.09 percentage points, and the gasoline research octane number (RON) increased by 0.6 units. The comprehensive performance of the catalyst can reach or exceed that of the natural-lamp-tube-based kaolin carrier. The results can not only provide guidance for the stable quality control of kaolin, but they can also significantly alleviate the resource restrictions for FCC catalyst production enterprises.